2016
DOI: 10.1002/pd.4958
|View full text |Cite
|
Sign up to set email alerts
|

Are ultrasound renal aspects associated with urinary biochemistry in fetuses with lower urinary tract obstruction?

Abstract: In LUTO, the ultrasound appearance of the fetal kidneys and urinary biochemistry are not correlated. It may be better to take both ultrasound and biochemistry into account when evaluating fetuses with fetal LUTO. © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 19 publications
0
21
0
1
Order By: Relevance
“…However, the systematic review examining this could not determine whether fetal urine measurements can provide a clinically accurate prediction of ultimate renal function . Furthermore, a recent study could not correlate the ultrasound appearance of the fetal kidneys and fetal urinary biochemistry …”
Section: Discussionmentioning
confidence: 99%
“…However, the systematic review examining this could not determine whether fetal urine measurements can provide a clinically accurate prediction of ultimate renal function . Furthermore, a recent study could not correlate the ultrasound appearance of the fetal kidneys and fetal urinary biochemistry …”
Section: Discussionmentioning
confidence: 99%
“…4 Fetal urine biochemistry has been assessed for its capacity to predict postnatal renal function in obstructive uropathy but has yielded controversial results. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] One recent meta-analysis concluded that no single analyte investigated to date could provide clinically relevant prognostic values to predict postnatal renal function. 17 This questionable utility of fetal urinalysis could in part be explained by disparity in methods of analysis, heterogeneity of uropathies, and heterogeneity of the criteria used for the evaluation of postnatal renal function.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are conflicting data on the diagnostic ability of biochemical analysis of the fetal urine in predicting fetal renal outcome . Furthermore, ultrasound parameters of the fetal kidney and urinary biochemistry are not correlated and should be taken separately into account when making a risk assessment for fetuses with LUTO …”
Section: Discussionmentioning
confidence: 99%